2009
DOI: 10.1002/ar.20943
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructure Changes of Cardiac Lymphatics During Cardiac Fibrosis in Hypertensive Rats

Abstract: Hypertension is one of the most common diseases that induce a series of pathological changes in different organs of the human body, especially in the heart. There is a wealth of evidence about blood vessels in hypertensive myocardium, but little is known about structural changes in the cardiac lymphatic system. To clarify the changes in structure of the cardiac lymphatic system during hypertension, we developed a hypertension animal model with Dahl S rats and we used Dahl R rats as the control group. We examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 26 publications
(26 reference statements)
0
6
0
Order By: Relevance
“…The lymphatic vasculature plays an important role in fluid homeostasis and immune regulation (38). Many studies have shown that cardiac lymphatic obstruction leads to myocardial edema, lymphangiectasis, and cardiac fibrosis and, ultimately, aggravates heart failure (7,21,24,26,29). Further studies have demonstrated that a blockade of this macrophagedriven regulatory response not only increases BP levels in the presence of salt-sensitive hypertension (31) but also converts the organism from a salt-resistant to a salt-sensitive state (30).…”
Section: Vegf-c; Vegfr-3; Left Ventricular Remodeling; Lymphangiogenementioning
confidence: 99%
See 1 more Smart Citation
“…The lymphatic vasculature plays an important role in fluid homeostasis and immune regulation (38). Many studies have shown that cardiac lymphatic obstruction leads to myocardial edema, lymphangiectasis, and cardiac fibrosis and, ultimately, aggravates heart failure (7,21,24,26,29). Further studies have demonstrated that a blockade of this macrophagedriven regulatory response not only increases BP levels in the presence of salt-sensitive hypertension (31) but also converts the organism from a salt-resistant to a salt-sensitive state (30).…”
Section: Vegf-c; Vegfr-3; Left Ventricular Remodeling; Lymphangiogenementioning
confidence: 99%
“…Evidence has shown that acute cardiac lymphatic obstruction leads to myocardial edema and local lymphangiectasis (7), and contributes to cardiac systolic and diastolic dysfunction (29). Chronic lymphatic obstruction leads to perivascular and interstitial fibrosis, causes cardiac structural and functional disorder, and ultimately leads to heart failure (21,24,26). Thus the lymphatic vessels may play a protective role against HS challengeinduced LV remodeling, which seems to be a buffering mechanism, and long-term HS intake may lead to this mechanism decompensation and will cause severe LV remodeling.…”
Section: H605mentioning
confidence: 99%
“…Myocardial hypertrophy is a common cardiovascular pathology, which is an independent risk factor of cardiovascular disease ( Cramariuc and Gerdts, 2016 ). Clinical and basic studies have shown that long-term high-salt intake is an independent risk factor of myocardial hypertrophy ( Mimran and du Cailar, 2008 ; Li et al, 2009 ). The study showed that salt-sensitive hypertensive patients were more prone to develop myocardial hypertrophy and cardiovascular events ( Chamarthi et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…VEGF-C causes hyperplasia of lymphatic capillaries, thus resolving salt-induced hypertension, suggesting that the lymphatic system may play an important role in regulation of blood pressure. Additional evidence showed that extensive lymphatic fibrosis has been observed in the hearts of the Dahl salt-sensitive rats fed a HSD, 3 indicating that hypertension induced by dietary salt can induce alteration of the lymphatic system. Since noninvasive, near-infrared fluorescence (NIRF) lymphatic imaging has been recently translated into the clinic, 4 we sought to evaluate whether it can be used as a tool to evaluate lymphatic responses to salt-induced hypertension and antihypertensive therapies.…”
mentioning
confidence: 97%